Prinsip Perencanaan dan Kriteria Pengendalian Pengembangan Fasilitas Rest-Area pada Jalan Tol di Indonesia: Planning Principles and Development Control Criteria of Rest Area Facilities on Toll Roads in Indonesia - Gede Windu Laskara (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2021)
Stopovers and relaxing facilities are important in intercity travel on toll roads. Long distances travel times in toll roads increase the supply and demand of these facilities in Indonesia. Not only the needs for refueling and resting, but also new support facilities demanded in rest area are often found, such as shopping, restaurant, worship place, and others. This phenomenon has attracted many investors to establish rest area with those complex facilities in term of business profit. To prevent negative impact of development and to protect main function of toll roads, this paper will discuss the planning and development control principles of rest areas located on toll roads in Indonesia. Analysis of components and criteria for rest areas on toll roads are generated by analyzing problems occurred. Site location, site area, accessibility, and main facilities specification are absolute factors, while zoning, circulation, road signage, and site utilities are conditional factors. The planning principles is to guarantee safety, security, and convenience of all activities in and around rest area and toll road. This research describes several criteria and components that should be controlled in order to achieve rest area planning principles that determined by qualitative methods.